2015
DOI: 10.18805/lr.v0iof.6783
|View full text |Cite
|
Sign up to set email alerts
|

Effect of planting date, seed rate and row spacing on nodulation efficiency of bold seeded spring mungbean [<italic>Vigna radiata</italic> (L.) Wilczek] in Bundelkhand region of India

Abstract: A field experiment was conducted during spring/summer season of 2007 and 2008 at Crop Research Centre of Institute of Agricultural Sciences, Bundelkhand University, Jhansi (U.P.) , to study the effect of planting date, seed rate and rows pacing on yield and yield attributes of bold seeded mungbean. Four planting dates (February 25, March 11, March 26 and April 10), three seed rates (30, 40 and 50 kg/ha) and two row spacing (20 cm and 30 cm) were tested. Grain yield increased with delay in planting up to March … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…These results are in line with those of Wafula et al (2021). Results were in contrary with those of Kumar et al (2016) who found non-significant effects due to spacing on nodule number in mung bean. Highest nodule number registered in the present study with seed rate of 105 kg ha -1 might be attributed to higher plant population and nitrogen demand in contrast to lower plant population under low seed rate.…”
Section: Resultssupporting
confidence: 86%
“…These results are in line with those of Wafula et al (2021). Results were in contrary with those of Kumar et al (2016) who found non-significant effects due to spacing on nodule number in mung bean. Highest nodule number registered in the present study with seed rate of 105 kg ha -1 might be attributed to higher plant population and nitrogen demand in contrast to lower plant population under low seed rate.…”
Section: Resultssupporting
confidence: 86%
“…Other findings are of Sethi et al (2015). Results were however, in contravention with findings of Thalji (2006) and Kumar et al, (2016) who found non-significant effects of spacing on nodules in faba beans and mung beans trials respectively. Although nitrates play a significant role in plant growth, many findings have revealed the need for minimal use in leguminous crops to encourage nodule formation.…”
Section: Number Of Nodules and Nodule Fresh Weightmentioning
confidence: 49%